Preparation of an amino functionalized Fe3O4/Gd2O3 network composite and application in electrochemical detection of Cu2+. Issue 2 (30th November 2015) - Sun, Xiao; Cai, Chuanjie; Liu, Tao; Zhang, Guilong; Cai, Dongqing; Xiong, Shiquan; Wu, Zhengyan
Abstract : A nano-network-structured amino functionalized Gd2 O3 /Fe3 O4 composite was prepared and used as a sensing platform to detect Cu 2+ . Abstract : A Fe3 O4 /Gd2 O3 nanocomposite grafted with polyethyleneimine (PEI) molecules was prepared using a one-pot synthesis method. Through this amino functionalized nanocomposite, a selective and ultra-trace electrochemical sensor for Cu 2+ was constructed. The electrochemical performances of the sensor were demonstrated by square wave anodic stripping voltammetry (SWASV). Parameters such as the supporting electrolyte, pH of solution, deposition time, and deposition potential for the sensor were optimized. The sensor linearly responded to Cu 2+ concentration in the wide range from 6 to 1680 nM with a detection limit of 0.4 nM (3δ method), indicating that this amino functionalized Fe3 O4 /Gd2 O3 composite could be a promising candidate material for the detection of Cu 2+ .